Familial stroke syndrome associated with mitral valve prolapse. - Rice, G; Boughner, DR; Stiller, C; Ebers, G (1980)
In a 27-member family, 8 individuals had mitral valve prolapse (MVP) by echocardiography. Four of them suffered a total of eight cerebral ischemic events in the first four decades of life. In none of these patients could risk factors for stroke, other than MVP, be found. Stroke did not occur in individuals free of MVP. This report draws attention to a previously unrecognized cause of familial stroke which strengthens the relationship between MVP and premature stroke.